Comparative Study of Chinese and International Standard Systems on Chemical Protective Clothing (Journal of Fiber Bioengineering and Informatics, 2013)
Through the comparative analysis of China's national and international standard systems on chemicalprotective clothing (CPC), this paper summarizes the differences in classification and minimumperformance requirements between several standard systems. The study provides the most basicperformance assessment factors for all types of CPC. It can also be observed that the standard systemsof European Standards (EN) and the International Organization for Standardization (ISO) have similarclassifications and performance requirements for CPC, while China's standard systems (GB) mainly givedetailed requirements for emergency team CPC as a supplement for previous international standards.
Keywords: Chemical Protective Clothing; Standard; Classification; Performance